A physiological signal database of children with different special needs for stress recognition - Coşkun, Buket; Ay, Şevket; Erol Barkana, Duygun; Bostancı, Hilal; Uzun, İsmail; Oktay, Ayşe Betül; Tunçel, Başak; Tarakçı, Devrim (Nature Research, 2023)
This study presents a new dataset AKTIVES for evaluating the methods for stress detection and game reaction using physiological signals. We collected data from 25 children with obstetric brachial plexus injury, dyslexia, and intellectual disabilities, and typically developed children during game therapy. A wristband was used to record physiological data (blood volume pulse (BVP), electrodermal activity (EDA), and skin temperature (ST)). Furthermore, the facial expressions of children were recorded. Three experts watched the children's videos, and physiological data is labeled "Stress/No Stress" and "Reaction/No Reaction", according to the videos. The technical validation supported high-quality signals and showed consistency between the experts.
Keywords: Stress Recognition; Special Needs; Physiological Signal Database